Word Formation of Consumable Items in Honkai: Star Rail Game - Sofie Nahendarani; Muhammad Rasyid Sulaiman; Eva Tuckyta Sari Sujatna (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
This study addresses the significance of understanding word formations for consumable items in the game Honkai: Star Rail. While previous literature identifies nine words formation techniques, their application to consumable item names in this game has not been thoroughly explored. To bridge this gap, we compiled 77 consumable item names that are in the game and analyzed it, utilizing in-game resources such as item descriptions. The analysis revealed that 17 items met our criteria for word formation analysis. We found that out of the nine theorized word formation techniques, only five techniques were identified in the word formation of item names. Most of the words used in forming the new consumable item names were associated with the consumable item's function or physical characteristics. However, the result of some names suggested a deeper connection to the game’s in-game lore. This research provides valuable insights into the naming process for objects, particularly in games, demonstrating that object names can carry linguistic or meaningful implications. In conclusion, this study enhances our understanding of word formations in the context of game item names, shedding light on aspects of the naming process, especially the linguistic aspect, and offering an example of a practical application of the naming of objects in differing contexts.